2021
DOI: 10.1007/s00405-020-06566-8
|View full text |Cite
|
Sign up to set email alerts
|

Auditory performance in a group of elderly patients after cochlear implantation

Abstract: Purpose The retrospective case review investigated the effect of cochlear implantation in subjects aged 61 years or older with respect to their auditory performance. The study also analysed the effect of age on the performance, and it drew a comparison between the outcomes of older and younger adults. Methods The outcome in a group of 446 patients aged 61 to 89 years at the time of unilateral cochlear implantation was compared with the outcome in a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Como ya se ha mencionado previamente, los pacientes en los que sí parece haber una disminución en los resultados auditivos, según diferentes estudios, son los mayores de 80 años. Giourgas et al 23 encontraron una diferencia estadísticamente significativa entre los sujetos que tenían 60-70 años y 80-90 años, al igual que en el estudio publicado por Roberts y cols 24 , donde los pacientes mayores de 80 años obtuvieron puntuaciones menores en la prueba de consonante-núcleo-consonante.…”
Section: Tabla 2 Resultados Obtenidos En Las Pruebas Verbales De Bisí...unclassified
“…Como ya se ha mencionado previamente, los pacientes en los que sí parece haber una disminución en los resultados auditivos, según diferentes estudios, son los mayores de 80 años. Giourgas et al 23 encontraron una diferencia estadísticamente significativa entre los sujetos que tenían 60-70 años y 80-90 años, al igual que en el estudio publicado por Roberts y cols 24 , donde los pacientes mayores de 80 años obtuvieron puntuaciones menores en la prueba de consonante-núcleo-consonante.…”
Section: Tabla 2 Resultados Obtenidos En Las Pruebas Verbales De Bisí...unclassified
“…Comorbidities without cognitive or neurological involvement (e.g., heart insufficiency and limited motor skills) also lead to less speech comprehension postoperatively. The more comorbidities an elderly person has, the less the postoperative speech comprehension develops with CI ( Giourgas et al, 2021 ). Knowledge of the individual presence of comorbidities and their treatment, such as medication, as well as knowledge of the influence on postoperative speech understanding is essential in clinical preoperative counseling for a CI.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation of speech comprehension has not been described by the authors, but to the complication rate, which does not differ significantly between younger and older patients even with comorbidities. Giourgas et al (2021) examined the effect of CI in 446 elderly patients at the age of 61 to 89 years during the time of unilateral CI (Group 1) with respect to their speech comprehension and compared the data with a randomized group of 110 adults at the age of 17-42 years (Group 2). There was no significant difference between Groups 1 and 2 related to their duration of hearing loss and score for comprehension of monosyllables preoperatively (Group 1: mean 6.6 ± 12.3%; Group 2: mean 5.0 ± 10.6%).…”
Section: Outcome and Comorbidities In The Elderlymentioning
confidence: 99%
“…In this study, even though the cutoff age of the elderly was older than in previous reports, speech recognition results in elderly patients under quiet conditions were as good as that in non-elderly patients ( Figure 1 ). Many studies have reported dramatic improvement in speech recognition after CI surgery in elderly patients [ 7 , 8 , 9 , 10 , 13 , 14 , 17 , 18 ]. They have shown that hearing under quiet conditions was not significantly different from non-elderly patients [ 7 , 11 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we only had the date of hearing ability in a quiet condition due to a lack of equipment in our facility for sound field tests in noisy condition, it has been widely reported that speech recognition in a noisy environment is more deficient in the elderly than in the non-elderly [ 9 , 14 , 15 , 18 ]. This finding is attributed to the decline in the central nervous system and cognitive function related to auditory processing under noisy conditions in the elderly.…”
Section: Discussionmentioning
confidence: 99%